2009
DOI: 10.1177/0022034509339889
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of IL-23 and the Th17 Pathway in Periodontitis

Abstract: Interleukin (IL)-23 is an essential cytokine involved in expansion of the Th17 lineage, which is associated with many immune-related destructive tissue diseases. We hypothesized that the IL-23-induced Th17 pathway plays a role in periodontal pathology and examined the expression of cytokines, and related molecules, in periodontal lesions and control sites. IL-23 and IL-12 were expressed at significantly higher levels in periodontal lesions than in control sites. However, the relative expression of the IL-23 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(165 citation statements)
references
References 34 publications
12
144
1
2
Order By: Relevance
“…Th17 lymphocytes, like Th1 cells, are also noted for their stimulatory role in osteoclastogenesis (Yago et al 2009). Th17 cells are observed in chronic periodontitis sites, and Th17 related cytokines are produced in periodontal lesions (Takahashi et al 2005, Vernal et al 2005, Ohyama et al 2009). …”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Th17 lymphocytes, like Th1 cells, are also noted for their stimulatory role in osteoclastogenesis (Yago et al 2009). Th17 cells are observed in chronic periodontitis sites, and Th17 related cytokines are produced in periodontal lesions (Takahashi et al 2005, Vernal et al 2005, Ohyama et al 2009). …”
Section: Adaptive Immunitymentioning
confidence: 99%
“…For example, it was reported that IL-17 is protective against Porphyromonas gingivalis-induced bone loss via mobilization of neutrophils in a murine model (Yu et al, 2007). However, clinical studies reported increased IL-17 levels associated with chronic periodontitis (Takahashi et al, 2005;Vernal et al, 2005;Ohyama et al, 2009). In addition, peripheral blood mononuclear cells from patients with gingivitis and periodontitis stimulated with outer membrane protein of P. gingivalis express IL-17 (Oda et al, 2003).…”
Section: Introduction Imentioning
confidence: 99%
“…En efecto, diversos estudios han asociado tanto una respuesta linfocitaria efectora tipo Th1 como una tipo Th2 a la progresión de la enfermedad periodontal (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) . Además, durante los últimos años, tanto el fenotipo Th17 como el Treg han sido implicados en la patogenia de la periodontitis (56)(57)(58)(59)(60)(61)(62)(63) . Trabajos previos de nuestro grupo de investigación han evidenciado una respuesta asociada tanto a un fenotipo Th1 como a un fenotipo Th17 durante la progresión de la periodontitis (35,44,57,64) .…”
Section: Discussionunclassified